Caracterização de materiais quaternários no ambiente de exceção em Mata Grande - AL - Gois, Laís Susana de Souza (2020)
Dynamic of the landscape studies are extremely important in geographic analyses, because, when it has the understanding of preterit phases by which passed the landscape, there is the possibility of building predictive models of scenarios, providing the understand of future and current dynamic. However, it is established that the analytic approach of landscape presupposes systematized studies, englobing integrated analysis of geologic, geomorphologic, climatic, pedologic and vegetational data set, as well as the anthropic influences. In this context, exception areas are excellent markers of preterit environmental register, because the occurrence of an area surrounded by completely different environmental sets allows regional comparatives of great quality. In this scenario, urges the importance of analyze the dynamic of landscape in Mata Grande’s intrusion, located in the homonymous town in the semiarid of Alagoas, area which has few proposes like this one, when compared with others States of Northeast of Brazil. This proposal resulted from systematic physical-environmental analyses in Mata Grande’s intrusion, electing slop deposits as one of the mainly focus. From literature review, geomorphological mapping and granulometric analysis, this research characterized slope deposits aiming to establish resemblances and particularities in relation to areas of humid enclaves (brejos) already studied and contributing with studies of local and regional environment analyses.